Auditoría operativa al area de servicio y su incidencia en el servicio externo de la compañía de transporte interprovincial Tia SA, cantón Quevedo, año 2013 - Osorio Hidalgo, Mery Elizabeth (2015)
Due to the process of globalization caused the increased needs of the people, giving rise to a number of hundred enterprises which transportation companies satisfying the needs of people moving from one point to another appear. It is therefore of great weight, was born in the city of Quito on September 15, 1965, the Company Interprovincial Transport TIA SA, rancheras type units, having received in the city of Quevedo. The company since its inception has been working with the Common box equals fair distribution of production, total income divided by the number of partners in equal parts. Since its inception has been driven by an innovative professional, who was able to stay in one of the best in the province. During its 48 years of existence the company has been clear that his purpose was serve and serve with excellence .......... What is excellence? Put the five senses in the person seeking contact, attention skills demand: who is unfit to serve is not suitable for understanding. In the process of the Operational Audit it was found that maintaining a low level of corrections to run on the operating area for an excellent mechanism in the company. In the same that appropriate recommendations are made to overcome the deficiencies found by the process.